Some Problems Concerning Vocational Training Curriculum for Hearing-Impaired People - Tran, Dũng (Journal of Technical Education Science, 2008)
Technical and vocational education plays an important role in the development of personality and gives valuable orientations for the deaf people. It provides them with a chance to be trained to become skillful people, enabling them to contribute greatly to society. Developing a training curriculum for the deaf people to help them get along with social life is therefore a real necessity to enable them to indentify themselves and increase their own value. Actually however, at our special vocational training centres for the handicapped, the curricula are not really appropriate. If we approach the problem suitably in the development of the curiculum, it will provide good conditions for the deaf maximize their ability to work so as to improve their lives. In developing an efficient curriculum for their training. researches are needed to find out what factors can have a meaningful impact on them.